C-reactive protein as the biomarker of choice to monitor the effects of exercise on inflammation in Parkinson’s disease - Mehta, Niyati; Luthra, Nijee S.; Corcos, Daniel M.; Fantuzzi, Giamila (Frontiers in Immunology, 2023)
Parkinson’s disease (PD), a heterogeneous disease with no disease-modifying treatments available, is the fastest growing neurological disease worldwide. Currently, physical exercise is the most promising treatment to slow disease progression, with evidence suggesting it is neuroprotective in animal models. The onset, progression, and symptom severity of PD are associated with low grade, chronic inflammation which can be quantified by measuring inflammatory biomarkers. In this perspective, we argue that C-reactive protein (CRP) should be used as the primary biomarker for monitoring inflammation and therefore disease progression and severity, particularly in studies examining the impact of an intervention on the signs and symptoms of PD. CRP is the most studied biomarker of inflammation, and it can be detected using relatively well-standardized assays with a wide range of detection, allowing for comparability across studies while generating robust data. An additional advantage of CRP is its ability to detect inflammation irrespective of its origin and specific pathways, an advantageous characteristic when the cause of inflammation remains unknown, such as PD and other chronic, heterogeneous diseases.